Understanding Biometric Identification for Indonesian Immigrant Families in Sanggar Belajar Sentul, Kuala Lumpur, Malaysia - Mustika Chasanatusy Syarifah; Bambang Edi Suwito; Hafid Algristian; Tri Deviasari Wulan; Diana Arum Lisnawati; Ken Putri Raudhatul Jannah; Zainul Hadi Wildan Ismail (Al-Qalam Institute, 2025)
The primary objective of this community service activity is to provide Indonesian Immigrant Workers (IIWs) with a fundamental understanding of biometric data. This study is significant due to the growing reliance on biometric systems across sectors and the vulnerability of IIWs, who often lack awareness of data security risks. Limited digital literacy and inadequate access to legal protections heighten their susceptibility to data misuse and breaches. The research employs a Community-Based Participatory Research (CBPR) approach, ensuring the involvement of stakeholders from Sanggar Belajar Sentul to design the activities, making them contextually relevant and addressing the specific needs of the target community. The community service successfully educated 23 Indonesian Immigrant Workers, increasing their awareness of the types of biometric data and the associated risks, particularly data leakage. The findings emphasise the importance of such educational initiatives in empowering vulnerable populations to safeguard their personal information. It is recommended that similar programs be expanded to other immigrant communities, integrating hands-on training and leveraging digital platforms for broader outreach. The contributions of this research include the effectiveness of community-based education in improving biometric data literacy and data protection awareness among immigrant workers, which can serve as a model for future educational interventions aimed at strengthening digital literacy in marginalised communities.